Experiences and satisfaction of high-risk mothers who gave birth in select facilities in Legazpi City, Philippines - Maria Stephanie Fay S. Cagayan MD; Veincent Christian F. Pepito; Rita Mae Ang Bon MD MPM; Erlidia F. Llamas-Clark (Intelektual Pustaka Media Utama, 2020)
Among the interventions implemented to curb maternal mortality in the Philippines, service delivery networks (SDNs) have been one of the most important. However, due to their recent implementation, frameworks to assess the quality of care they provide have not yet been established. To address this need, we had formulated the Integrated Patient-Centered Health Service Framework and used it to explore the satisfaction of mothers who gave birth in select facilities Legazpi City Philippines. We conducted key-informant interviews with 14 mothers. We found out that they were satisfied with the quality of care during pre-pregnancy, pregnancy, and post-partum; however, the quality of care during labor and delivery, adherence to referral protocols, and respect for patient‟s autonomy can still be improved. The framework should be used by program managers to have a qualitative measure of quality of care provided by SDNs, as well as to ensure that referral protocols were implemented.